Understanding the affinity between components of wood-plastic composites from a surface energy perspective - Oporto, Gloria S.; Gardner, Douglas J.; Kızıltaş, Alper; Neivandt, David J. (My University, 2011)
To evaluate surface compatibility inwood-plastic composites (WPCs), the dispersion and acid-base components of surface energy of various thermoplastic resins (matrices) and several wood-based reinforcing materials were determined using inverse gas chromatography (IGC). Polypropylene (PP), nylon 6, poly(ethylene terephthalate) (PET), poly(trimethyl terephthalate) (PTT), high impact polystyrene (HIPS), and styrene maleic anhydride (SMA) were used as thermoplastic resins while wood flour (hot water extracted and un-extracted), microcrystalline cellulose (MCC) (50μm and 907mu;m), α-cellulose (60μm), and silicified microcrystalline cellulose (SMCC) (60μm) were used as reinforcing materials. All matrices and reinforcing components were exposed to low vapor concentrations of apolar (decane, heptane,nonane,octane) and polar(chloroform, ethyl acetate, dichloromethane, acetone, and tetrahydrofuran) probes. Methane and helium were employed as reference and carrier gases, respectively.IGC retention times were used to determine the acid-base component of surface energy of the analyzed materials. The corresponding surface energy, work of adhesion, and work of cohesionwere calculated based on the van Oss-Chaudhury-Good approach (acid-base and Lifshitz-van der Waals interactions). Composite performance was analyzed by measuring tensile and flexural strengths according to ASTM standards. The results indicated that for the same type of filler (assuming similar shape and dimensions), the mechanical properties of the composites increased when the ratio of the work of adhesion to the work of cohesion increased. A similar trend was observed when the thermoplastic resin employed to create the composite possessed an acid-base component of surface energy greater than zero.
Annual Technical Conference - ANTEC, Conference Proceedings
Keywords: Extracted wood flour; Inverse gas chromatography; Microcrystalline cellulose; Surface energy; Thermoplastic resins; Wood-plastic composites; Work of adhesion; Work of cohesion; Odun unu özütü; Ters gaz kromatografisi; Mikrokristalin selüloz; Yüzey enerjisi; Termoplastik reçineler; Ahşap-plastik kompozitler; Yapışma işi; Kohezyon işi